Analysis of E-Lkpd Needs Based On Geographical Inquiry To Stimulate Students™ Collaborative Abilities - Purnamasari, Wulan Safriani; Astina, I Komang; Suharto, Yusuf; Sumarmi, Sumarmi; Soekamto, Hadi; Setyasih, Iya' (Tunas Geografi, 2024)
Collaborative abilities are one of the pillars that students must have in facing the complexity of the world, especially in world complexity, especially in abilities that can be trained by using E-LKPD in learning. Therefore, this research aims to determine the needs analysis for E-LKPD development. This type of research is quantitative and descriptive, using questionnaires, interviews, and observation data collection techniques. The research subjects were students in class XI-10 IPS at SMA Negeri 5 Samarinda. The data obtained was then analyzed using quantitative descriptive analysis techniques. Based on the data analysis, the curriculum requires LKPD as an attachment that must be provided in learning. The material presented in E-LKPD has informative and procedural characteristics. The analysis of student needs shows that 78% of students need  E-LKPD, making it easier for them to understand the material, and 38% of students attract students' learning attention. Regarding the weaknesses of the E-LKPD used during geography learning, it is that the E-LKPD is not in accordance with the meaning of the E-LKPD itself, the E-LKPD is not in accordance with the curriculum used, the E-LKPD used by students has not attracted the students' learning attention. Based on the results of this research can provide an illustration that needs analysis seen from the curriculum aspect, material characteristics, and student characteristics is the main step in developing E-LKPD that is appropriate and innovative based on current needs. Keywords: Need analysis; E-LKPD Bases on Geographical Inquiry; Collaborative Abilities